A challenge to the second law of thermodynamics from cognitive science and vice versa. - Hemmo, Meir; Shenker, Orly (Synthese, 2021)
We show that the so-called Multiple-Computations Theorem in cognitive science and philosophy of mind challenges Landauer's Principle in physics. Since the orthodox wisdom in statistical physics is that Landauer's Principle is implied by, or is the mechanical equivalent of, the Second Law of thermodynamics, our argument shows that the Multiple-Computations Theorem challenges the universal validity of the Second Law of thermodynamics itself. We construct two examples of computations carried out by one and the same dynamical process with respect to which Landauer's principle implies contradictory predictions concerning the entropy increase. Our two examples are based on a weak version of the Multiple-Computations Theorem, which is quite uncontroversial, and therefore they amount to a clear refutation of the universal validity of Landauer's Principle. We consider some responses to this argument that do not attempt to single out one computation over the others, and we show that they do not work. We further consider ways out of the argument by externalist approaches supporting the computational theory of the mind who propose that the interaction of a computing system with the environment is enough to select a single computation over the others. We show on physical grounds that this approach fails too. We then reverse the direction of our challenge and formulate a dilemma for supporters of the computational theory of the mind: (i) they must reject (or amend somehow) the causal closure of physic; or else (ii) they must accept on a priori grounds that Landauer's Principle and the Second Law of thermodynamics are not universally valid. Finally, we present our version of a type–type mind-brain identity theory called Flat Physicalism, which is based on the paradigm case of statistical mechanics, and we show that it circumvents the challenge from Landauer's Principle and the Multiple-Computations Theorem and does not fall prey to our dilemma.